2018
DOI: 10.1186/s13287-018-0952-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Endothelial progenitor cell-derived exosomes, loaded with miR-126, promoted deep vein thrombosis resolution and recanalization

Abstract: BackgroundDeep vein thrombosis (DVT) is caused by blood clotting in the deep veins. Thrombosis resolution and recanalization can be accelerated by endothelial progenitor cells. In this report, we investigated the effects of miR-126-loaded EPC-derived exosomes (miR-126-Exo) on EPCs function and venous thrombus resolution.MethodsIn vitro promotional effect of miR-126-Exo on the migration and tube incorporation ability of EPCs was investigated via transwell assay and tube formation assay. In addition, a mouse ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Recent studies have supported the use of exosomes as promising alternatives for stem cell therapy [37]. EPC-Exos have been demonstrated to protect endothelial function in kidney injury, acute lung injury, and sepsis models; promote deep vein thrombosis resolution and artery re-endothelialization; and induce angiogenesis in skin wound healing [25, 3840]. We therefore evaluated the effects of EPC-Exos on osteogenesis and consolidation in a rat tibial DO model, with EPCs as positive control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have supported the use of exosomes as promising alternatives for stem cell therapy [37]. EPC-Exos have been demonstrated to protect endothelial function in kidney injury, acute lung injury, and sepsis models; promote deep vein thrombosis resolution and artery re-endothelialization; and induce angiogenesis in skin wound healing [25, 3840]. We therefore evaluated the effects of EPC-Exos on osteogenesis and consolidation in a rat tibial DO model, with EPCs as positive control.…”
Section: Discussionmentioning
confidence: 99%
“…Only normal EPC-Exos were investigated in this study. The limitation of this study is that the reported advantages of exosomes for drug or RNA delivery [38, 43] were not considered in the present study; hence, EPC-Exos modified to stimulate both osteogenesis and angiogenesis warrant further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…26 Our previous studies have demonstrated that miRNAs have a vital role in EPC function. 11,[27][28][29][30] Additionally, miR-205 has been shown to have different effects on angiogenesis and migration in different types of tumours. [32][33][34][35]42 Meanwhile, miR-205 promotes wound healing in human corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, angiogenesis and thrombolysis are crucial for thrombus recanalization. [11][12][13] Numerous studies have shown that endothelial progenitor cells (EPCs) are recruited to the thrombus to accelerate thrombus resolution and play a vital role in physiological and pathological neovascularization in adults. 12,[14][15][16] Moreover, EPCs can differentiate into endothelial cells to participate in angiogenesis and thus are a promising therapeutic approach for thrombus resolution as there is only limited success with the current treatment options.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation